34. EVALUATION OF URINARY RETENTION IN POSTPARTUM WOMEN AND ITS MANAGEMENT AT CENTRAL OBSTETRICS HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the urinary retention of postpartum women and the treatment attitude at the Department of General Obstetrics, National hospital of Obstetrics and Gynecology in 2024. Comment on some factors related to urinary retention of postpartum women in the study group.Subjects and methods: The cross-sectional descriptive study design to collect imformation of monitoring, treatment, care under care of 180 woman after childbirth at the Department of General Obstetrics, National hospital of Obstetrics and Gynecology from 01/01/2024 đến 31/05/2024.Results: The average time of urinary retention after birth was 20.75 ± 9.88 hours; 100% of urinary retention were guided bladder catheter intervention, used smooth muscle strengthening drugs, used pain relievers and anti-inflammatory drugs; 98,3% were used bladder catheter placement, and Glycerin Borate pump; 15% of post-birth pregnant women had to keep a bladder catheter to care for and monitor their urination. As a result of treatment, 95% of post-birth women have normal urination; 3.3% of them were referred to urologists and oriental medicine specialists. 4 main factors related to difficulty urinating after birth status were the duration of labor over 15 hours; pain during labor; the weight of the fetus and postpartum movement is not correct, the differences were statistically significant with p-values
Keywords: urinary retention; postpartum women; treatment attitude